Pemberdayaan Masyarakat Melalui Revitalisasi Fungsi Karang Taruna dan PKK Desa Pembakulan Kabupaten Hulu Sungai Tengah - Hawini, Medika Iri; Varinia Pura Damaiyanti; Ahmad Fauzi Fikri; Bainah; Della Fadila; Johanson Nobel; Mikha; Pasha Aulia Tsabitha; Rahmadina Rizky Aulia; Rianita; Rifky Bagus Aditiya; Virginia Claudia Liwo Suan (Prodi Sosiologi FISIP ULM, 2025)
Village groups have an important role in improving the welfare of village communities, developing the potential of the young generation, and strengthening solidarity at the village level. Village groups are the driving force needed to hold the key to community empowerment management. However, the village group in Pembakulan village has long been no longer running. In fact, with the existence of youth organizations and PKK, community integrity can be grown so as to overcome social problems such as poverty, low education, health, and low quality of human resources. Apart from that, it is also to increase partner empowerment with various activities held in collaboration with parties outside the village. For this reason, it is important to revitalize the Karang Taruna and PKK village groups. The number of participants who participated was 15 people. The service was held from July to September in Pembakulan Village, East Batang Alai District, Hulu Sungai Tengah Regency. The method for implementing village group revitalization is using the live-in method through a participatory approach and directly involving local communities and government institutions. Implementation of activities begins with socialization and continues with a Forum Group Discussion which focuses on solidarity activities held in the village. The results of service activities show that the Pembakulan Village Karang Taruna group is able to understand and implement the function of village groups to create positive and sustainable change through involvement in activities for teenagers in the village to increase solidarity and a sense of social concern.